The Term Structure of Interest Rates and the Demand for Investment - Hartman, Richard C. (Quarterly Journal of Economics, 1980)
This paper examines the question of whether long-term or short-term interest rates should appear in investment demand functions. Three basic models are examined. The first involves a distribution of time lags required to complete investment projects; the second is based on a simple adjustment-costs model; and the third incorporates uncertainty and risk aversion. The major conclusion is that, except for some special cases which are probably quite unrealistic, both long-term and short-term interest rates affect investment demand.